Periodontal Health and Microbiological Characteristics of Siwak (Chewing Stick) and Toothbrush Users: A Cross-Sectional Study - Yasmin, Winarni; Vaithilingam, Rathna Devi; Halib, Nadia; Mohamad Hanafiah, Rohazila; Ramli, Haslinda (European Journal of General Dentistry, 2024)
Objective Siwak is a chewing stick used to clean the teeth and oral structures. Many studies have been conducted to assess the potential use of siwak in dentistry and concluded that it can be an alternative to a toothbrush in reducing plaque and gingivitis. However, some observations have reported more periodontal attachment loss and gingival recession among siwak users. This study aimed to compare the periodontal health and oral microbial characteristics between siwak and toothbrush users.Materials and Methods This was a cross-sectional study, and participants were recruited from the public who attended community engagement programs. They were assigned to two groups based on whether they used siwak or a toothbrush. Participants who consented were examined for periodontal health. Supragingival and subgingival plaque samples were collected for bacterial identification and quantification.Statistical Analysis The SPSS package version 21.0 was used for data entry. Data normality was statistically tested using Kolmogorov–Smirnov and Shapiro–Wilk tests, while data comparison used either t-test or Mann–Whitney U test.Results A total of 36 participants were included in this study. The findings revealed that the plaque scores, bleeding scores, and periodontal pocket depths between siwak and toothbrush users were comparable (p > 0.05). Both groups had no evidence of gingival recession. Most participants had bacteria with characteristics of Streptococcus spp., which were present in 12 toothbrush users and 6 siwak users.Conclusions The periodontal health status of siwak users was comparable to that of toothbrush users. Despite this, siwak users had fewer types of bacteria than toothbrush users, suggesting that siwak may serve as an alternative device to conventional toothbrushes for oral hygiene when properly used.
Keywords: bacterial morphology; chewing stick; gingivitis; periodontal pocket; Salvadora persica